KARAKTERISTIK MINYAK ATSIRI DARI DAGING BUAH PALA MELALUI BEBERAPA TEKNOLOGI PROSES - Sipahelut, Sophia G.; Telussa, Ivonne (Universitas Sebelas Maret (UNS), 2011)
In Maluku, nutmeg and mace are considered valuable market commodities, while the pod are wasted andleft in the field. The research aimed to expand and to characterize the quality of the nutmeg-pod oil by someprocess technology (methods of drying and distillation). Drying of sliced nutmeg pod either under shade, in thesun, or using cabinet dryer were carried out followed by distillation process either using water distillation orwater-steam distillation. Physical characteristics (refraction index and solubility in 90% alcohol), myristicincompound and oil yields of the essential oil resulted from those process combinations were analyzed. Resultindicated that the highest yield was obtained (1.65 g) from the combination of drying under shade and watersteam distillation. The refraction index and solubility in 90% ethanol of the extracted oils were all in the rangeof the SNI Quality Standard. There were about 21 different components in the oil of nutmeg pod. The level ofmyristicin (the valuable component) was much higher than that found in the nutmeg.